2020
DOI: 10.3390/ijms21145171
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Epigallocatechin-3-Gallate (EGCG) in Diseases with Uncontrolled Immune Activation: Could Such a Scenario Be Helpful to Counteract COVID-19?

Abstract: Some coronavirus disease 2019 (COVID-19) patients develop acute pneumonia which can result in a cytokine storm syndrome in response to Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) infection. The most effective anti-inflammatory drugs employed so far in severe COVID-19 belong to the cytokine-directed biological agents, widely used in the management of many autoimmune diseases. In this paper we analyze the efficacy of epigallocatechin 3-gallate (EGCG), the most abundant ingredient in green tea le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 132 publications
(176 reference statements)
2
62
0
Order By: Relevance
“…6 ). These herbs contain flavonoids (myricetin from litchi chinensis seed) ( 44 ), flavan-3-ol (catechin and epigallocatechin gallate from tea and Spatholobus root) ( 45 , 46 ), caffeic acid derivatives [caftaric acid and chlorogenic acid ( 47 ) from purple coneflower or honeysuckle flower bud or chia seed ( 48 )] ( SI Appendix , Fig. S2 ), and whether they are related to the antiviral activity remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). These herbs contain flavonoids (myricetin from litchi chinensis seed) ( 44 ), flavan-3-ol (catechin and epigallocatechin gallate from tea and Spatholobus root) ( 45 , 46 ), caffeic acid derivatives [caftaric acid and chlorogenic acid ( 47 ) from purple coneflower or honeysuckle flower bud or chia seed ( 48 )] ( SI Appendix , Fig. S2 ), and whether they are related to the antiviral activity remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In this aspect, EGCG is potentially a promising agent for COVID-19 to revert hyperinflammation. Previous studies have demonstrated that EGCG can strongly inhibit the JAK/STAT pathway regulating the synthesis and secretion of several cytokines and chemokines [ 58 , 59 ]. Moreover, EGCG can suppress the canonical NF-κB pathway [ 60 , 61 ], which plays a key regulatory role in the expression of proinflammatory cytokines including IL-1, TNF-α, IL8, IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, EGCG is protective in diseases with uncontrolled immune activation, thus, may ameliorate severity of COVID-19 13 since the latter is related to overreaction of the immune system. 14 Altogether these results suggest that green tea catechins could reduce overall risks related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%